2016
DOI: 10.2197/ipsjjip.24.732
|View full text |Cite
|
Sign up to set email alerts
|

Informatics Concepts and Computational Thinking in K-12 Education: A Lithuanian Perspective

Abstract: Informatics or Computer Science is important subject in nowadays school education. Informatics can be presented as a discipline for understanding technology in a deeper way-the understanding behind computer programs. Bringing Informatics to schools means preparing young people to be creators of information technology-not only to be users of technological devices. To achieve that, we need to introduce Informatics concepts to primary, basic (K-9) and secondary education (K-12). From the other side, we need to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 11 publications
0
12
0
10
Order By: Relevance
“…Furthermore, they are selected as good Bebras tasks and used in some countries. Actually, It was reported that a problem made by a student was one of the most interesting tasks among students in Lithuania (Dagienė et. al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they are selected as good Bebras tasks and used in some countries. Actually, It was reported that a problem made by a student was one of the most interesting tasks among students in Lithuania (Dagienė et. al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, many authors believe (Dagienė and Futschek, 2010;Dagienė et al, 2015;Dagienė and Stupurienė, 2016;Forišek and Winczer, 2006;Kalas and Tomcsanyiova, 2009;Kubica and Radoszewski, 2010) that by means of informatics competitions, we can present various parts and used concepts of computer science. Competitions like Olympiad in informatics, Bebras and many others have been the result of this line of thinking.…”
Section: History Of Correspondence Seminarsmentioning
confidence: 99%
“…CS concepts play a central role for understanding fundamentals of computers, information technology, software, hardware and other devices. However, in practice, very often the training of skills in application software is given much more room at schools than to discover and going deeper into concepts of CS (Dagiene and Stupuriene, 2016a). CS education should be taken seriously and combine various forces.…”
Section: Focus On Cs Conceptsmentioning
confidence: 99%
“…For the Lithuanian case, the questionnaire was sent to about 650 IT/CS teachers (usually IT teachers teach CS as well in lower secondary schools), and was answered by 337 of them (about 52%). Results from the questionnaire in depth are presented in paper by Dagiene and Stupuriene (2016a). Below we present the questions from the questionnaire along with a summary of the teachers' answers.…”
Section: Teachers' Attitudes Towards the Cs Curriculummentioning
confidence: 99%